PHYTOCHEMICAL SCREENING, ANTI-OXIDANT POTENTIAL AND ANTIMICROBIAL ACTIVITIES IN THREE SPECIES OF CESTRUM PLANTS - PRASAD M.P.; APOORVA PRABHU; APOORVA PRABHU; MONICA SINGH THAKUR; YOGESH M. RUPAREL (International Journal of Pharma and Bio Sciences, 2013)
Plants have richest source of bioactive compounds as phytochemicals in the form of secondary metabolites. In this study three Cestrum species C. aurantiacum, C. nocturnum and C. diurnum were investigated for phytochemicals and revealed presence of Alkaloids, Anthraquinones, Cardiac Glycosides, Carbohydrates, Flavonoids, Phenolic compound, Tannins and Terpenoids. Antioxidant potential was estimated by DPPH and FRAP assay and C. diurnum showed higher antioxidant potential than that of the other two species in both assays. Different solvents such as ethanol, methanol, butanol, propanol and acetone were used to extract the bioactive compounds from the leaves of these plant species. The antimicrobial activity of these solvent extracts was tested against three bacterial (S. typhi, P. aeruginosa and K. pneumoniae) and two fungal species (Aspergillus and Trichoderma) by agar well diffusion method. C. aurantiacum showed maximum antibacterial activity, and maximum antifungal activity was detected for butanol extract of C. nocturnum against Aspergillus.